AL-AF’AL DAN PRINSIP-PRINSIP PENGAJARANNYA (BERDASARKAN WAKTU PENGGUNAANNYA DAN JUMLAH HURUFNYA) - Jabir, Muh. (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
Nahw's foundation of science is the Qur'an, hadith, verse, and Arabic expression which is believed to be true. The scholars endured this burden with considerable sincerity. The cause of the compilation of the science of Nahw is the occurrence of errors in reading the Qurâ€™an and speaks the language. The first cleric to attempt to correct the mistakes committed by Muslims at the time, was Abu al-Aswad al-Duali (w 69 H). The work done by Abu al-Aswad al-Duali, is to punctuate the qurâ€™an, as a sign of raf ', nasb, jarr, and jazm. The effort of Abu al-Aswad al-Duali in spelling the Qur'anic punctuation is seen as an attempt in the field of Nahw science and not an attempt in the form of a book or book that is composed and contains the problems of Nahw or grammar. The work in the form of the book was done by the scholars who came after it, after seeing the efforts made by Abu al-Aswad al-Duali. The scholars who succeeded in composing Nahw's science in the form of a book, Isa Bin Umar al-Saqafi (w 149 H), with two books each titled KitÄb al-JÄmi 'and KitÄb al-Mukmil, al-Khalil bin Ahmad al-Farahidi (175) with his work KitÄb al-'Ain, Sibawaih (188 H) with his work KitÄb Sibawaih and Qutrub (d 206 H) with his book KitÄb al-'Ial FÄ« al-Nahw.